2021
DOI: 10.1111/jcpp.13408
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Schizophrenia prevention and prodromal psychosis in children and adolescents

Abstract: Catalan and colleagues aggregated findings related to detection, prognosis, and intervention in Clinical High Risk for Psychosis (CHR‐P) children and adolescents through October 7, 2019 (Catalan et al., 2020). While a sufficient number of studies were available to meta‐analytically summarize evidence on detection and prognosis, the authors highlight the need for more studies on interventions, including cognitive behavioral therapy for psychosis, in CHR‐P youth. Further research on the biological and neural cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As the potential for early screening grows, the need for discussion and effectiveness testing of specific interventions for different risk groups also grows. We found that SSD and neurodevelopmental disorders can be discriminated with sufficient accuracy considering CPSS risk, which can be easily measured in the clinical setting, can be combined with other test items (such as cognitive tests, neuropsychological tests, inflammatory markers, brain morphological imaging) (15, 41,44,45) and can be used for clinical diagnosis in the future. Differentiating children with psychosis risk from those with developmental disorders in childhood is difficult and is one of the most important challenges in child psychiatry.…”
Section: Differentiation Between the Psychosis Risk Group And Those W...mentioning
confidence: 96%
“…As the potential for early screening grows, the need for discussion and effectiveness testing of specific interventions for different risk groups also grows. We found that SSD and neurodevelopmental disorders can be discriminated with sufficient accuracy considering CPSS risk, which can be easily measured in the clinical setting, can be combined with other test items (such as cognitive tests, neuropsychological tests, inflammatory markers, brain morphological imaging) (15, 41,44,45) and can be used for clinical diagnosis in the future. Differentiating children with psychosis risk from those with developmental disorders in childhood is difficult and is one of the most important challenges in child psychiatry.…”
Section: Differentiation Between the Psychosis Risk Group And Those W...mentioning
confidence: 96%
“…Schizophrenia is a mental disorder characterized by hallucinations, alterations in cognition, behavior, emotion, and disorganized speech that severely cause distress and daily functional impairment [1,2]. Approximately 23 million people worldwide are suffering from schizophrenia, 1% of whom are in adolescence or early adulthood [3,4]. Moreover, the early mortality of schizophrenia patients is still high regarding patients' age [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Children who already needed additional support to make progress in their education, including children with reading disorders, have been hardest hit by school closures. Although not the focus of the review by Catalan et al, Taylor and Huque (2021) note that racial and ethnic minority youth are diagnosed with psychotic disorders at significantly higher rates than nonminority youth. In the United States, the Black Lives Matter protests have focused attention on the role that discrimination and racial injustice play as stressors in the lives of youth of color, with implications for mental health.…”
mentioning
confidence: 99%